2018
DOI: 10.1186/s13287-018-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin rescued interleukin 1β-impaired chondrogenesis of human mesenchymal stem cells

Abstract: BackgroundOsteoarthritis (OA) is a widespread arthritic disease and a primary cause of disability. Increasing evidence suggests that inflammation has a pivotal part in its pathogenesis. Interleukin-1β (IL-1β) is a primary mediator of local inflammatory processes in OA. Current therapies for OA mainly focus on the symptoms of the advanced stage of the disease. The possible utilization of bone marrow mesenchymal stem cells (BMSCs) to regenerate cartilage is an appealing method, but in the case of OA requires cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 38 publications
1
72
0
Order By: Relevance
“…However, treatment with melatonin promoted the expression of cartilage ECM at both the mRNA and protein levels, even in the presence of IL-1β. SOX9 plays an important role in chondrogenesis by regulating matrix protein synthesis during neocartilage formation [18]. Consistent with previous studies, we found that melatonin significantly increased the level of transcriptional factor SOX9 even in IL-1β-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…However, treatment with melatonin promoted the expression of cartilage ECM at both the mRNA and protein levels, even in the presence of IL-1β. SOX9 plays an important role in chondrogenesis by regulating matrix protein synthesis during neocartilage formation [18]. Consistent with previous studies, we found that melatonin significantly increased the level of transcriptional factor SOX9 even in IL-1β-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have demonstrated that melatonin priming can induce chondrogenic differentiation of MSC [ 148 150 ]. Melatonin-primed MSC greatly improved renal function in the diabetic nephropathy model, which was correlated with autophagy activation [ 151 ].…”
Section: Msc Priming With Other Moleculesmentioning
confidence: 99%
“…OA pathogenesis remains poorly understood, although it is established that synovium inflammation has a pivotal part in its pathogenesis [ 19 ], which highlights the importance of synovium-targeted therapy in this disease [ 6 , 20 ]. Adhesion molecules in the synovial lining assist with monocyte infiltration into inflamed OA synovium [ 14 ].…”
Section: Discussionmentioning
confidence: 99%